2018
DOI: 10.1038/s41598-018-32447-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite accumulation and metabolic network in developing roots of Rehmannia glutinosa reveals its root developmental mechanism and quality

Abstract: Rehmannia glutinosa root contains many compounds with important medicinal properties and nutritional benefits, but only more than 140 compounds have been reported so far. Many other compounds and their accumulation and metabolic networks during its development remain unclear. In order to clarify them, its metabolic profiles at three different developmental stages were analyzed using untargeted LC-MS analysis. Multivariate analysis revealed that 434 metabolites differently accumulated in its different stages, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Anyway, NAA treatment could affect the contents of some metabolites in R. glutinosa, suggesting some change in its quality. On the other hand, these result of our current study also indicated that LC-MS technology had a potential to identify many metabolites in R. glutinosa as stated by previous reports [1,2], but could not identify any metabolite in R. glutinosa.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Anyway, NAA treatment could affect the contents of some metabolites in R. glutinosa, suggesting some change in its quality. On the other hand, these result of our current study also indicated that LC-MS technology had a potential to identify many metabolites in R. glutinosa as stated by previous reports [1,2], but could not identify any metabolite in R. glutinosa.…”
Section: Discussionsupporting
confidence: 47%
“…For the samples with biological replicates: Prior to differential gene expression analysis, for each sequenced library, the read counts were adjusted by edgeR program package through one scaling normalized factor. Differential expression analysis of two samples was performed using the EBSeq R package [2]. The resulting FDR (false discovery rate) were adjusted using the PPDE(posterior probability of being DE).…”
Section: Quanti Cation Of Gene Expression Levels and Differential Expmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain cases, Rehmannia glutinosa has also been used to treat diabetes, anemia and urinary tract infections ( 17 ). A previous study extracted the effective component in Rehmannia glutinosa and identified it as catalpol, whose molecular formula is C 15 H 22 O 10 ( 18 ). Studies have since revealed that catalpol exhibits anti-inïŹ‚ammatory and anti-apoptotic effects ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those variables with a relative standard deviation (RSD) below 30% in the QC samples analyses were kept for further data processing. Then, the resulting data were normalized to the total peak area of each sample using Microsoft Excel 2007 software (Microsoft, Redmond, WA, USA) (Tan et al., ; Xiong et al., ; Zhou et al., ). The acquired Excel file with three dimension data sets including m/z, peak RT and peak intensities, and RT–m/z pairs were used as the identifier for each ion.…”
Section: Methodsmentioning
confidence: 99%